Factors predicting individual health behaviors during Covid-19 pandemic (Revista de Investigaciones Universidad del Quindío, 2021)
Background: Covid - 19 is a global pandemic, affecting all areas of social life in every country. In the current conditions of the Covid-19 pandemic, individual health behaviors are of primary importance. Each citizen consciously implements their health behaviors not only to prevent them from being infected but also to help the country's prevention of Covid-19 effective. The study of factors predicting people’s health behaviors in the community will help managers come up with appropriate measures to improve public health and to quickly repel the pandemic.Objectives: The research analyzes factors predicting personal health behaviors during the Covid-19 pandemic in Vietnam, including: pandemic awareness, self-assessment of the possibility of becoming infected, fear of disease, quality of life, and mental health (anxiety).Methods:  This was a cross-sectional quantitative study. Data were collected from a convenient sample of 572 people in Vietnam (118 males, 451 females; M age =27.0 (sd = 10.0) ) by a means of an online questionnaire survey. The questionnaire was constructed based on the YouGov Behavior Change questionnaire; the Fear of Coronavirus-19 Scale (FCV-19), WHOQOL-BREF, the Moral Foundation Questionnaire, and Knowledge of Covid-19. This study performed multivariate regression analysis to explore effects of moral, quality of life, knowledge and fear of Coronavirus-19 on health behaviors of participants.Result: The result showed that fear and sex factors explain 4% (R2-adj = 4%) of health behavior change in the Covid-19 pandemic. In addition, there is a signìicant relationship between health behaviors and fear, age, gender, and occupation.Conclusion: People's health behaviors are particularly concerned during the Covid-19 pandemic. Community healthcare activities for the people should be tailored to suit different population groups such as gender, age or emotional experiences. More in-depth studies are needed to find out the causes of these differences, thereby proposing practical solutions to help people practice more effective health behaviors, contributing to preventing and combating the outbreak.
Keywords: Covid – 19; predictors; health behaviors; people in the community